Risk factors for anxiety and its impacts on acute exacerbation in older patients with chronic obstructive pulmonary disease - Mou, Yan; Shan, Lin; Liu, Yunhuan; Wang, Yue; He, Zhengming; Li, Xiangyang; Zhu, Huili; Ge, Haiyan (Frontiers in Medicine, 2024)
Background Anxiety is common in patients with chronic obstructive pulmonary disease (COPD), especially in older patients with the definition of age over 60 years old. Few studies have focused on anxiety in older COPD patients. This study aimed to analyze the risk factors of anxiety in older COPD patients and the impacts of anxiety on future acute exacerbation. Methods The general information, questionnaire data, previous acute exacerbation and pulmonary function were collected. Hamilton Anxiety Rating Scale (HAMA) was used to evaluate the anxiety of older COPD patients. The patients were followed up for one year, the number and the degrees of acute exacerbations of COPD were recorded. Results A total of 424 older COPD patients were included in the analysis. 19.81% (N = 84) had anxiety symptoms, and 80.19% (N = 340) had no anxiety symptoms. There were increased pack-years, more comorbidities, and more previous acute exacerbations in older COPD patients with anxiety compared to those without anxiety (P < 0.05). Meanwhile, a higher modified Medical Research Council (mMRC), a higher COPD assessment test (CAT) score and a shorter six-minute walking distance (6MWD) were found in older COPD patients with anxiety (P < 0.05). The BODE index, mMRC, CAT score, comorbidities and acute exacerbations were associated with anxiety. Eventually, anxiety will increase the risk of future acute exacerbation in older COPD patients (OR = 4.250, 95% CI: 2.369–7.626). Conclusion Older COPD patients with anxiety had worsening symptoms, more comorbidities and frequent acute exacerbation. Meanwhile, anxiety may increase the risk of acute exacerbation in the future. Therefore, interventions should be provided to reduce the risk of anxiety in older COPD patients at an early stage.